Finding the beat entrainment, rhythmic play, and social meaning in rock music - Hesselink, Nathan (New York Bloomsbury Academic, 2022)
Introduces entrainment-the capacity to perceive a beat and synchronize to it-through the lens of contemporary rock music to explain why humans enjoy listening to music together and what is it about certain beats that captures our attention"--
Preamble -- Ambiguity, Rhythm, and Participation in Radiohead's "Pyramid Song" -- Rhythmic Play, Compositional Intent, and Communication in Rock Music -- The Backbeat as Expressive Device in Rock Music -- Entrainment and the Human-Technology Interface, Historical and Technological Considerations -- Entrainment and the Human-Technology Interface, Sociological and Aesthetic Considerations -- Radiohead, Oxford, and a Rhythmic Holy Grail.
includes bibliographical references and index.
description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Click tracks; Musical meter and rhythm; Rock music -- Analysis, appreciation